Impact of Backreflections on Single-fiber Bidirectional Wavelength-Division-Multiplexing Passive Optical Networks (WDM-PONs) - Gao, Shiyu (Université d'Ottawa / University of Ottawa, 2013)
With increased demand for bandwidth-hungry applications such as video-on-demand, wavelength-division-multiplexing passive optical network (WDM-PON) has become a strong contender in overcoming the last mile bottle neck. However, the wide-scale deployment of WDM-PONs has been delayed mainly due to the high cost of wavelength-specific optical components. To realize cost-effective WDM-PONs, various wavelength-independent, so called colorless architectures, have been developed so that all the subscribers can have identical optical network units (ONUs). In such WDM-PONs, however, single-fiber bidirectional transmission results in degradation of system performance caused by interference between the signals and backreflections. This thesis investigates the impact of backreflections on single-fiber bidirectional WDM-PONs. A WDM-PON with various optical line terminals (OLTs) and colorless ONU configurations is presented. The dependence of the power penalty, caused by backreflections, on a variety of parameters is investigated. This includes parameters such as the source linewidths, receiver bandwidth, transmission line loss (TLL), ONU gain, chirp effect at the ONU and optical return loss (ORL), in various WDM-PON configurations. The WDM-PON with continuous wave (CW) seed light and remodulation schemes are both presented and studied experimentally. The impacts of the backreflections on the single-fiber bidirectional WDM-PON with various OLT and ONU configurations are compared and analyzed accordingly.
Keywords: backreflection; beat noise; linewidth; optimum gain; power penalty